Changing Patterns in Low-Income Country Financing and Implications for Fund Policies on External Financing and Debt. (Policy Papers; Policy Paper ;, 2009)
Low-income countries (LICs) face significant challenges in meeting their development objectives while maintaining a sustainable debt position. The international community's main answer to this dilemma has been to promote recourse to concessional external resources. The Fund's recommendations to LICs conform to this preference: the practice in Fund-supported programs in LICs has generally been to set zero limits on nonconcessional external borrowing while not restricting concessional financing, although flexibility has been applied on a case-by-case basis to allow some nonconcessional borrowing when warranted.